The impact of the ursodeoxycholic acid as monotherapy and in the combination with the lactulose on the biochemical blood tests values of the nonalcoholic steatohepatitis patients - I. V. Mayev; Yu. A. Kucheryavyy; S. V. Morozov; M. G. Saidullayeva; M. L. Akhtayeva; N. Yu. Stukova; E. A. Krasnyakova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of the Study. The administration of ursodeoxycholic acid (UDCA) as monotherapy or in combination with lactulose for the treatment of the patients with nonalcoholic steatohepatitis (NASH) has been studied insufficiently. The aim was to assess the impact of the 90-day therapy with Ursoliv® drug (20 mg/kg per day of the UDCA and 25 mg/kg per day of the lactulose) on the biochemical blood tests values of the NASH patients in comparison with the Ursosan® drug (20 mg/kg per day of UDCA).Мaterials and methods. 60 patients with the NASH were included into the open randomized prospective comparative study without applying control. The patients were separated into 2 equal groups. The 1st group was administered Ursoliv®, and the 2nd group – Ursosan®. The baseline laboratory tests – markers of cytolysis and cholestasis, lipid profiles – and after 45 and 90 days of the treatment were assessed.Results. The credible dynamic of the biochemical tests values of the cytolysis as compared with the baseline (the reducing of the activity of the alanine transaminase and the aspartate transaminase) and of the cholestasis (gamma-glutamyl transpeptidase) was observed; the positive changes in the lipid profile (the increase in the concentration of the high density lipoproteins and the reduction in the total cholesterol, the low density lipoproteins, the very low density lipoproteins and triglycerides ) were seen during the treatmet in both groups. The tendency towards the more expressed impact of the combination of UDCA and lactulose (Ursoliv®) in comparison to the monotherapy by UDCA (Ursosan®) on the biochemical parameters were discovered. However, the statistical credibility was not reached, which, probably, can be explained by the peculiarities of the sampling.Conclusions. The administration of the UDCA in the dosage of 20 mg/kg per day as monotherapy as well as in the combination with the lactulose (25 mg/kg per day) in the patients with NASH is characterized by the expressed positive impact on the laboratory markers of cytolysis, cholestasis and the lipid profile. The higher dosages of the UDCA and of the UDCA in combination with the lactulose can be recommended for the treatment of the NASH patients.